2002
DOI: 10.1076/apab.110.1.74.905
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Regulation of Pituitary Receptors for Vasopressin and Corticotropin Releasing Hormone

Abstract: At least two hypothalamic peptides, corticotropin releasing hormone (CRH) and vasopressin (VP), are important in regulating adrenocorticotropin (ACTH) release from the anterior pituitary. Both are secreted in a pulsatile manner and stimulate ACTH secretion by interacting with G protein-coupled receptors (GPCRs), namely the type 1 CRH receptor and V1b receptor, respectively. Repeated or prolonged stimulation with either peptide can cause reduced ACTH responsiveness or desensitisation, both in vivo and in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Repeated or prolonged stimulation with CRH reduces CRH receptor binding and can cause reduced ACTH responsiveness or desensitization [31]. Indeed chronically activated corticotrophs generally show blunted ACTH response to CRH [32].…”
Section: Resultsmentioning
confidence: 99%
“…Repeated or prolonged stimulation with CRH reduces CRH receptor binding and can cause reduced ACTH responsiveness or desensitization [31]. Indeed chronically activated corticotrophs generally show blunted ACTH response to CRH [32].…”
Section: Resultsmentioning
confidence: 99%
“…We also found that CRF stimulates the expression level of POMC mRNA and secretion of ACTH in anterior lobe cells, while vasopressin stimulates the secretion of ACTH but not the expression of POMC mRNA in accordance with previous reports (Giguere & Labrie 1982, Aguilera et al 1983. The adenylate cyclaseprotein kinase A (PKA) pathway mediates CRF-induced secretion of POMC-derived peptides, while AVP increases the secretion of POMC-derived peptides via the phospholipase C (PLC)-protein kinase C (PKC) pathway (Mason et al 2002), indicating the intracellular signaling cascade under CRF is different from that under vasopressin. It therefore seems that the secretion of Ucn 2 is dependent on the adenylate cyclase-PKA pathway, while that of POMCderived peptides is dependent on either the adenylate cyclase-PKA or PLC-PKC pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a number of G protein-coupled hormone receptors respond physiologically to pulsatile administration of ligand rather than to steady state levels [30], we examined the effects of VIP (1 and 5 nmol) given intermittently by i.p. injection over 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Several G protein-coupled receptors respond physiologically to pulsatile administration of their cognate ligands, rather than to steady-state levels [30]. In addition, a recent study by Abad et al reported the therapeutic and prophylactic effects of VIP delivered intraperitoneally in mice with TNBS colitis [27].…”
Section: Intermittent Intraperitoneal Vip In Tnbs Colitismentioning
confidence: 99%